2018
DOI: 10.1016/j.enconman.2018.04.086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotating twisted tape on thermo-hydraulic performances of nanofluids in heat-exchanger systems

Abstract: Stable TiO 2 -H 2 O nanofluids are prepared and their stabilities are studied. An experimental set for studying the heat transfer and flow characteristics of nanofluids is established. Heat transfer and flow characteristics of TiO 2 -H 2 O nanofluids in a circular tube with rotating and static built-in twisted tapes are experimentally investigated and compared. An innovative performance evaluation plot of exergy efficiency is developed and the exergy efficiency of tube with rotating and static built-in twisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 44 publications
5
32
0
1
Order By: Relevance
“…The results demonstrated that the low-to-high PR twisted tape yielded an increasing trend of η as Re increased. However, the maximum η value of the low-to-high twisted tape was lower than those of other modifications, such as RGPR and rotation of the twisted tape [23]. This is due to differences in terms of other parameters that influenced the system's performance.…”
Section: Introductionmentioning
confidence: 85%
“…The results demonstrated that the low-to-high PR twisted tape yielded an increasing trend of η as Re increased. However, the maximum η value of the low-to-high twisted tape was lower than those of other modifications, such as RGPR and rotation of the twisted tape [23]. This is due to differences in terms of other parameters that influenced the system's performance.…”
Section: Introductionmentioning
confidence: 85%
“…This compelled the researcher to do a comprehensive thermo‐hydraulic performance analysis of the problem and to achieve an optimal working condition of the problem. A comprehensive performance index of the problem was formulated by using thermal and exergy efficiency theories . The best‐suited condition for the problem was identified from the formulated equation of comprehensive performance index, to get the maximum HT and least increase in Δ p of the working fluid.…”
Section: Challenges With Nanofluidsmentioning
confidence: 99%
“…A parameter (exergy efficiency) describing the "quality" of energy is proposed to guide this work. The equation of exergy efficiency is presented 55 :…”
Section: Theoretical Calculationmentioning
confidence: 99%